Comprehension strategy instruction for Hispanic children with mathematical learning difficulties - Orosco, Michael J.; Mamedova, Shahlo; Abdulrahim, Naheed A. (Frontiers in Psychology, 2025)
Hispanic children face significant problem-solving challenges due to the simultaneous linguistic and cognitive demands of mathematics. This study examined the effectiveness of comprehension strategy instruction (CSI) for Hispanic children and investigated working memory as a potential moderator of intervention effectiveness. Participants included 43 third-grade Hispanic children with mathematical learning difficulties and 32 control peers from an urban public school system in the southwestern United States. Using hierarchical linear modeling, results demonstrated significant effects of CSI on mathematical performance, with medium effect sizes across multiple assessments. An interaction model revealed that both CSI and working memory were significant predictors of mathematical achievement, with a marginally significant two-way interaction implying that students’ cognitive profiles moderated the impact of the intervention. Findings highlight the importance of integrating CSI into mathematics instruction for Hispanic students to support both linguistic and cognitive development.